UJI FITOKIMIA DAN GC-MS BUAH API-API (Avicennia marina (FORSSK.) VIERH) - Andrian Fernandes; Rahimahyuni Fatmi Noor’an (Jurnal Insan Farmasi Indonesia, 2019)
Api-api (Avicennia marina (Forssk.) Vierh) is one of the species found in Barat Muara Kaeli Research and Education Forest. Traditionally, Api-api fruit stew water in China is used for the treatment of fever, sore throat and dysentery, while modern Api-api fruits have been used as food products. This study aims to determine the phytochemical component and predict the chemical content using GC-MS from Api-api fruit (Avicennia marina (Forssk.) Vierh) as a basic consideration use of derivative product. The Api-api fruit was obtained from the Api-api tree at the coordinates N 0°23'55.31" and E 117°25'33.55", then macerated using 96% ethanol. The concentrated 96% ethanol maceration results were then tested for phytochemicals and GC-MS. Api-api (Avicennia marina (Forssk.) Vierh) fruit phytochemical test results contained flavonoids, triterpenoids and steroids. Based on GC-MS test results on Api-api (Avicennia marina (Forssk.) Vierh) fruit contained γ-sitosterol (C29H55O) as much as 13.68%, dibutyl phthalate (C16H22O4) as much as 13.42%, Palmitic acid, ethyl esters (C18H36O2) of 7.85%, 9,12-Octadecadienoic acid, ethyl ester (C20H36O2) of 7.56% and Linolenic acid, ethyl ester (C20H34O2) of 6.33%, undecane (C11H24) of 7.25 %, 2-Propenamide, N-(1-cyclohexylethyl) at 6.78%, and several other minor compounds.